2021
DOI: 10.1029/2021jb021940
|View full text |Cite
|
Sign up to set email alerts
|

Infrasound Radiation From Impulsive Volcanic Eruptions: Nonlinear Aeroacoustic 2D Simulations

Abstract: Infrasound observations are increasingly used to constrain properties of volcanic eruptions. In order to better interpret infrasound observations, however, there is a need to better understand the relationship between eruption properties and sound generation. Here we perform two‐dimensional computational aeroacoustic simulations where we solve the compressible Navier‐Stokes equations for pure‐air with a large‐eddy simulation approximation. We simulate idealized impulsive volcanic eruptions where the exit veloc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 121 publications
1
11
0
Order By: Relevance
“…Ichihara et al (2009) discusses a related case of lake water surface explosions (not confined by conduit walls). In addition, our source is conceptually similar to the directed blast numerical simulations of Watson et al (2021). We note that Watson et al (2021) observed enhanced high frequencies in the downstream blast direction (i.e., above the vertically directed source), consistent with our observations.…”
Section: Discussionsupporting
confidence: 88%
“…Ichihara et al (2009) discusses a related case of lake water surface explosions (not confined by conduit walls). In addition, our source is conceptually similar to the directed blast numerical simulations of Watson et al (2021). We note that Watson et al (2021) observed enhanced high frequencies in the downstream blast direction (i.e., above the vertically directed source), consistent with our observations.…”
Section: Discussionsupporting
confidence: 88%
“…There is an opportunity to use simulations of the eruptive jet and atmospheric response (Cerminara et al., 2016; Koyaguchi et al., 2018; Ogden et al., 2008; Watson et al., 2021) as part of the forward modeling workflow to bypass assumptions and biases that may be introduced when using simple source models (e.g., point monopoles or dipoles; point mass, energy, and momentum sources) that are only indirectly linked to eruptive processes. To pursue this approach, we must develop coupled models of conduit flow and the response of a compressible atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Matoza et al 2009aMatoza et al , 2013. Numerical simulations (Taddeucci et al 2014;Cerminara et al 2016;Brogi et al 2018;Watson et al 2021a) and laboratory studies (Swanson et al 2018;Peña Fernández et al 2020) have examined volcanic jets, which are complex, directional sources, and provide a first step towards more realistic source models. Significant advances are likely to come from adapting and integrating results from modern aeroacoustic and jet noise studies into the volcano infrasound community (Matoza et al 2009a), as well as from combining simulation and laboratory results with field observations to investigate infrasound source processes and quantify uncertainties.…”
Section: Volcanic Sourcesmentioning
confidence: 99%
“…Elevation contour units are meters. Modified from Fee et al (2021) demonstrated that neglecting nonlinear effects may result in inaccurate infrasound-derived estimates of eruption properties (Anderson 2018;Brogi et al 2018;Dragoni and Santoro 2020;Maher et al 2020;Watson et al 2021a). For example, aeroacoustic simulations by Watson et al (2021a) show that changes to waveform shape due to nonlinear effects can lead to underestimation of total erupted volume (Fig.…”
Section: Infrasound Propagationmentioning
confidence: 99%
See 1 more Smart Citation